Assessment of health literacy of adult residents within Sampaloc, Manila - Aleria, Maria Carla Q.
Health literacy has been a constant area of interest especially among highly developed nations. Several studies have been done in developed countries to measure functional health literacy and determine factors that affect its across various populations. However there is limited data regarding health literacy in developing countries. This study aimed to evaluate the health literacy of adult residents within Sampaloc, Manila. A total of 385 respondents were asked to answer health literacy assessment tools. Associations between sociodemographic characteristics and health literacy were determined using both parametric and nonparametric statistical tests. Results revealed mean scores of 5.72 (SD=1.84) which implies at risk for poor word recognition health literacy, and 1.59 (SD=1.50) which indicates high likelihood of limited numeracy and comprehension health literacy. Word recognition health literacy was significantly associated with sociodemographic characteristic specifically education, annual family income, civil status, employment status, and health insurance status. Similarly, numeracy and comprehension health literacy was ifluenced by education, annual family income, civil status, employment status, health insurance status and age. Mean self-perceived health literacy score was 14.45 (SD=2.69), indicating marginal health literacy. The self-perceived health literacy scores were positively correlated with performance-based health scores. Low health literacy scores can imply decreased understanding of medications and disease conditions, poor medication adherence and increased miscommunication of health care provider and the patient.